Restless rancher - Ryan, Jennifer, 1973- (Ryan, Jennifer, 1973- Wild rose ranch., 2019)
"One minute down-on-his-luck rancher Austin Hubbard slept soundly, the next, a sassy spitfire dumped a pitcher of water on his head and woke him up--in more ways than one. Hired to help him rebuild his ranch, Sonya Tucker ends up helping him put the tattered pieces of his life back together. The capable, all-business accountant is on a mission to get the ranch up and running, but can he convince the temptingly beautiful woman to take a chance on him? Sonya was dismayed that Austin had lost it all: money, family, respectability. Things she--who'd been raised by her mother at Nevada's notorious brothel Wild Rose Ranch--only dreamed about. But working with the long, lean cowboy shows her that Austin is honorable to his core. Together they slowly grow to see what the love between them might bring. But then Austin's powder keg of a family feud explodes, exposing long-buried secrets, and threatening their new-found love..." -- Amazon.